Ethylene Glycol Mediated Facile and Controlled Growth of Ultralong Hexagonal Silver Molybdate Microrods - Singh, D; Montero-Aravena, M; Manquián-Villalobos, C (Elsevier B.V., 2018)
A controlled growth of nano/micro rods with defined morphologies are of great interest due to its special and unique properties. Here we report ethylene glycol mediated facile and controlled synthesis of ultra-long (∼100 μm) perfect hexagon shaped microrods of silver molybdate by a cost effective method of hydrothermal. The exact conditions are optimized by varying the effective parameters. The synthesis involves the mixing of different concentration of silver nitrate solution (0.025, 0.075, 0.125 M) with ammonium molybdate in the presence of 10 ml of ethylene glycol and then post hydrothermal treatment at 150 °C for 12 hrs. Only 0.075 M conc. of silver nitrate results perfect hexagons whereas the lower and higher concentrations result the formation of distorted edge shaped and longer microrods of Ag6Mo10O33. The magnetic measurement shows the perfect diamagnetic behavior of these mircorods. © 2017 Elsevier B.V.